Nonel approaches in the field of gastric cancer surgical treatment - Kirkilevsky, S.; Polyasny, V.; Mashukov, A.; Kovalevskaya, L. (Journal of Education, Health and Sport, 2022)
The aim of the study: to estimate the impact of different cellular phenotype of gastric tumors on the survival of patients treated according to standard protocols. Object and methods of research.The work presents the results of a study conducted on the basis of two medical institutions - the National Cancer Institute and the abdominal oncology and surgery department of the Odessa Regional Oncology Center. 221 patients underwent surgery for gastric cancer (GC) in the period 2007-2013. The average age of patients was 60.88 ± 10.5 years, men - 180, women - 41. Of the total number of operated, 143 patients underwent surgery in the amount of gastrectomy, 78 - subtotal distal resection. Results. All patients included in the study underwent radical surgery. Tumors removed during surgery were examined using histological, cytological, immunohistochemical methods and genetic tests. The obtained results are monitored for the presence/absence of clinical parallels and mathematical correlations. It was concluded that some combinations of immunohistochemical (IHC) markers were effective in separating groups of patients with different biology of gastric cancer. Conclusions. Performing more advanced operations (including the use of D2 lymph dissections) is the most effective option for surgical treatment of microsatellite-unstable and Epstein-Barr virus-associated gastric cancer.